2007
DOI: 10.1007/s10461-007-9256-1
|View full text |Cite
|
Sign up to set email alerts
|

Start Talking About Risks: Development of a Motivational Interviewing-Based Safer Sex Program for People Living with HIV

Abstract: The epidemiology of HIV infection in the US in general, and in the southeast, in particular, has shifted dramatically over the past two decades, increasingly affecting women and minorities. The site for our intervention was an infectious diseases clinic based at a university hospital serving over 1,300 HIV-infected patients in North Carolina. Our patient population is diverse and reflects the trends seen more broadly in the epidemic in the southeast and in North Carolina. Practicing safer sex is a complex beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…Clients also responded positively to exercises and narratives, which provided opportunities to build specific practical skills for practicing safer sex, including use of barrier methods and communication skills. These findings are consistent with components emphasized in many other ''prevention with positives'' programs [23][24][25]30 but suggest that 242 GOLIN ET AL.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Clients also responded positively to exercises and narratives, which provided opportunities to build specific practical skills for practicing safer sex, including use of barrier methods and communication skills. These findings are consistent with components emphasized in many other ''prevention with positives'' programs [23][24][25]30 but suggest that 242 GOLIN ET AL.…”
Section: Discussionsupporting
confidence: 82%
“…38 The program emphasizes setting small realistic goals focused on harm reduction. 30 The 13-step protocol is summarized in Table 1.…”
Section: Overview Of the Safetalk Program And Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…DiIorio et al, 2003;Golin et al, 2006;Parsons, Golub, Rosof, & Holder, 2007) and for HIV risk reduction in both HIV-negative and positive populations (e.g. Belcher et al, 1998;Golin et al, 2007;Naar-King et al, 2006). In South Africa, MI has successfully been used as part of an intervention to reduce sexual risk behaviours in clients attending an STI clinic (Simbayi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is in accordance with the findings for an interview study with client of an STI clinic who received MI-based counseling. 33 These clients indicated that they considered the approach to be respectful and nonjudgmental. A further major advantage of MI-based counseling was the way in which MI-based, effective counseling can be introduced in real-life STI clinics.…”
Section: Discussionmentioning
confidence: 99%